Costanzo Festa’s (?) motet ‘O altitudo divitiarum’ re-examined: new suggestions regarding its source context, attribution and function - Wojciech Odoj (Muzyka)
In the manuscript VatS 38, copied around 1550–63, there are two anonymous motets: Gaude felix ecclesia (ff. 114v-122r) and O altitudo divitiarum (ff. 122v-126r). Joseph Llorens attributed them to Costanzo Festa (c. 1490–1545) in his catalogue of the musical manuscripts of the Sistine Chapel and both are included in Festa’s Opera omnia. What Llorens apparently missed is the fact that the former, with the text Gaude felix Florentia and attributed to Andreas de Silva – who probably wrote it in honor of Pope Leo X on the occasion of his election in 1513 – appears in the manuscript RomeV 35-40 (the Vallicelliana Manuscript). The analysis of O altitudo divitiarum, on the other hand, its stylistic features, transmission, and liturgical and historical context has made me suggest that the motet, if indeed by Festa, may have been intended for the peace treaty in Nice in 1538 with participation of Pope Paul III, Emperor Charles V, and King Francis I of France. If so, it could be considered as a companion to Cristóbal de Morales’s six-voice motet in two movements Jubilate Deo omnis terra which was specifically written for this occasion.